1992
DOI: 10.1016/0169-5983(92)90059-6
|View full text |Cite
|
Sign up to set email alerts
|

On the use of the Weierstrass-Mandelbrot function to describe the fractal component of turbulent velocity

Abstract: It is shown that the Weierstrass-Mandelbrot function simulates the irregularity in a turbulent velocity record and yields correct forms for the energy and dissipation spectra. In particular, the universal properties of a corresponding multi-fractal function are demonstrated by showing its ability to reproduce and explain turbulent flow spectra measured near the walls of straight and curved channels and in the obstructed space between a pair of disks corotating in an axisymmetric enclosure. The simulation capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 21 publications
0
21
0
1
Order By: Relevance
“…(39) needs to be convergent which yields α = 2 as for the Laplacian (17). To determine β we have to demand that u(x, t) is a Fourier transformable field 5 .…”
Section: The Physical Chain Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…(39) needs to be convergent which yields α = 2 as for the Laplacian (17). To determine β we have to demand that u(x, t) is a Fourier transformable field 5 .…”
Section: The Physical Chain Modelmentioning
confidence: 99%
“…In this way we avoid the appearance of a characteristic length scale in our chain model. It seems there are analogue situations in turbulence [17] and other areas where the present interdisciplinary approach could be useful.…”
Section: Introductionmentioning
confidence: 99%
“…Fractal geometric study of the Weierstrass function (as a mono-fractal) and its generalization has an interesting literature, both in theory and in applications [6,17,18,28]. Although in the present work, we have studied the local fractional derivative, non-local based fractional studies of f are reported [23].…”
Section: If F (α) Is Continuous Then It Does Not Vanish Aementioning
confidence: 98%
“…The fractional Brownian motion simulation method can be further classified into the midpoint-displacement method, the Poisson Faulting method and Successive random additions method [28][29][30]. In particular, the midpoint displacement (MD) method and the Weierstrass-Mandelbrot (WM) fractal function method are the most commonly used fractal methods [31][32][33] by researchers. These fractal methods have often shown substantial differences in their form features and statistical properties [34,35].…”
Section: Introductionmentioning
confidence: 99%